1952
DOI: 10.2307/4587981
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Invertebrates as Indicators of Stream Pollution

Abstract: Year-round field studies of the biology of stream sanitation were initiated by the biology section of the Public Health Service's Environmental Health Center on Lytle Creek in October 1949. The aims of these investigations were: 1. To develop or devise and field test procedures and equipment for biological surveys and investigations of polluted streams. 2. To investigate seasonal and diurnal environmental changes in a stream polluted with oxygen-depleting wastes. 3. To determine how the physical-chemical envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
1
2

Year Published

1968
1968
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 2 publications
3
43
1
2
Order By: Relevance
“…Above the point of discharge gill breathing aquatic insects predominated (i.e. Plecoptera, Ephemeroptera and Trichoptera) indicating high quality (Gaufin 1956). Downstream, the increased concen tration of organic matter from the effluent resulted in an increase in the decomposer component of the ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Above the point of discharge gill breathing aquatic insects predominated (i.e. Plecoptera, Ephemeroptera and Trichoptera) indicating high quality (Gaufin 1956). Downstream, the increased concen tration of organic matter from the effluent resulted in an increase in the decomposer component of the ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the water quality of streams can reflect increased nutrient loads associated with sewage discharge and probably, to a lesser degree and agricultural runoff (Gaufin and Tarzwell, 1956;Gaufin, 1958;Olive and Dambach, 1973). In this study, the observed decreases in dissolved oxygen levels from SS2 to SS6 indicated a potential increased organic load in the stream.…”
Section: Discussionmentioning
confidence: 99%
“…De son côté BERTHELEMY, 1966, après avoir comparé la répartition de 32 de ces espèces rencontrées d'amont en aval dans les torrents pyrénéens avec celle donnée par WINKLER, estime que « la similitude entre les deux classements est nette, les zones amont étant, en effet, les moins polluées ». Cependant le système de KOLKWITZ et MARSON n'est plus guère utilisé car il est l'objet de nombreuses critiques (GAUFIN et TARZWELL, 1956, HAVRANEK, 1966, ZELINKA et MARVAN, 1966. Il ne saurait, en effet, résister sans de profondes retouches à un examen approfondi, tant d'ordre chimique que bactériologique et biologique.…”
Section: Les Zones De Saprobiesunclassified